Diagnosis of Ancylostomiasis in a Cat - Ridho Gelagar, Ario; Aulia Tri Yuska, Dian; Ramadhan, Juliadi; Zukiaturrahmah, Anna; Aulia, Usma; Sukmawati, Yofa (Basic and Applied Nursing Research Journal, 2025)
Ancylostomiasis is an important gastrointestinal helminthiasis in cats with zoonotic potential. This case report describes ancylostomiasis in a seven-year-old domestic female cat presented to Yours Animal Clinic, Padang Panjang, West Sumatra, with diarrhea and lethargy. Clinical examination, fecal analysis, and hematological evaluation were performed to establish the diagnosis. Fecal examination using native smear, flotation, centrifugation, and McMaster counting techniques revealed Ancylostoma sp. eggs with an eggs-per-gram (EPG) value of 2,200, indicating a mild infection intensity. Physical examination showed a low body condition score, dull hair coat, mild dehydration, and diarrhea. Hematological analysis demonstrated decreased red blood cell count, hemoglobin, hematocrit, granulocytes, and platelets, accompanied by increased lymphocytes, monocytes, mean corpuscular hemoglobin (MCH), and mean corpuscular hemoglobin concentration (MCHC), consistent with anemia and an inflammatory response secondary to helminth infection. Based on these findings, the cat was diagnosed with ancylostomiasis and treated with anthelmintics, fluid therapy, antibiotics, and supportive care. This case highlights the integration of clinical, parasitological, and hematological findings in the diagnosis of ancylostomiasis in cats and underscores the importance of routine deworming, appropriate husbandry, environmental sanitation, and periodic fecal examination to reduce the risk of infection and potential zoonotic transmission.